Попередження кризових явищ на підприємстві засобами санації та реструктуризації - Перерва, Петро Григорович; Кобєлєва, Тетяна Олександрівна; Товажнянський, Вячеслав Леонідович (НТУ "ХПІ", 2015)
У статті розглянуто методичні підходи до визначення кризових явищ на машинобудівних підприємствах в рамках системи антикризового управління. Розроблено пропозиції щодо запобігання кризових явищ з використанням засобів санації та реструктуризації. Сформовано пропозиції по практичному використанню розроблених заходів на промислових підприємствах.

The article considers methodical approaches to definition of the crisis phenomena in engineering enterprises in the framework of a crisis management system. It is proved that the emergence of crisis situations that can lead to bankruptcy of enterprises is an integral feature of market economy. Proposals for the prevention of the crisis phenomena by means of readjustment and restructuring. The article substantiates the thesis that for more effective to prevent bankruptcy, it is necessary to solve the problem of implementation of efficient, adapted to local conditions mechanisms for determining the likelihood of bankruptcy even before the emergence of obvious signs of insolvency of the company, as well as to create an appropriate system of monitoring of enterprises at the level of region or industry. Proposals on practical use of the developed measures in industrial enterprises.
The prevention of the crisis phenomena at the enterprise by means of reorganization and restructuring
Keywords: менеджмент антикризовий; машинобудування; ефективність економічна; crisis management; machine-building enterprises